Integrating time in public policy: Empirical description of gender-specific outcomes and budgeting - Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2014)
Incorporating time in public policymaking is an elusive area of research. Despite the fact that gender budgeting is emerging as a significant tool to analyze the socioeconomic impacts of fiscal policies and thus identify their impacts on gender equity, the integration of time-use statistics in this process remains incomplete, or is even entirely absent, in most countries. If gender budgeting is predominantly based on the index-based empirical description of gender-specific outcomes, a reexamination of the construction of the gender (inequality) index is needed. This is necessary if we are to avoid an incomplete description of the gender-specific outcomes in budget policymaking. Further, "hard-to-price" services are hardly analyzed in public policymaking. This issue is all the more revealing, as the available gender-inequality index - based on health, empowerment, and labor market participation - so far has not integrated time-use statistics in its calculations. From a public finance perspective, the gender budgeting process often rests on the assumption that mainstream expenditures, such as public infrastructure, are nonrival in nature, and that applying a gender lens to these expenditures is not feasible. This argument is refuted by time budget statistics. The time budget data reveal that this argument is often flawed, as there is an intrinsic gender dimension to nonrival expenditures.
Keywords: D13; J22; H31; 330; Unpaid Care Work; Fiscal Policy; Gender Budgeting; Time Use; Macro Policy